2011
DOI: 10.1038/jes.2011.38
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biomarkers of occupational jet fuel exposure among air force personnel

Abstract: There is a potential for widespread occupational exposure to jet fuel among military and civilian personnel. Urinary metabolites of naphthalene have been suggested for use as short-term biomarkers of exposure to jet fuel (jet propulsion fuel 8 (JP8)). In this study, urinary biomarkers of JP8 were evaluated among US Air Force personnel. Personnel (n ¼ 24) were divided a priori into high, moderate, and low exposure groups. Pre-and post-shift urine samples were collected from each worker over three workdays and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…7,8 Previous studies have reported significant associations between postshift urinary naphthol concentrations and personal work shift exposure to JP-8 and smoking. 9,10 Because of the various compounds present in JP-8, several urinary metabolites may be used as biomarkers of exposure to JP-8.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…7,8 Previous studies have reported significant associations between postshift urinary naphthol concentrations and personal work shift exposure to JP-8 and smoking. 9,10 Because of the various compounds present in JP-8, several urinary metabolites may be used as biomarkers of exposure to JP-8.…”
mentioning
confidence: 98%
“…We previously characterized urinary naphthols in a pilot study of 24 workers at one USAF base, 7 but here we report the results from a larger follow-up study of 73 workers at three USAF bases that includes additional urinary metabolites and evaluates the potential role of GST polymorphisms. The Occupational JP8 Exposure Neuroepidemiology Study was designed to investigate the relationship between exposure to JP-8 and neurological outcomes, 13 using the exposure assessment data presented here.…”
mentioning
confidence: 99%
“…Personal exposure assessment has proved challenging because of the complex composition of JP-8, and has focused on using surrogate measures of exposure including self-reported exposure 2,3 and biomarkers of exposure. [2][3][4][5][6][7][8][9][10][11][12] These studies have shown a wide range in the levels of exposure to JP-8 among US Air Force (USAF) personnel, with the highest occurring among those who report routine occupational exposure to jet fuel.…”
mentioning
confidence: 99%
“…2,3 Similarly, previous studies have demonstrated that THCs in personal air samples were associated with other biomarkers of JP-8 exposure, including levels of volatile organic compounds (VOCs) in exhaled breath 4,7,9 and 1-and 2-napthols in urine. 6,[9][10][11][12] Although these exposure assessment methods are noninvasive, certain methods only monitor a single route of exposure, and differences among individuals and dynamic environmental factors only permit approximating body burden of VOCs and their metabolites.…”
mentioning
confidence: 99%
“…After controlling for work shift smoking, measurements of blood volatile organic compounds (ethylbenzene, toluene, xylene) are higher among US Air Force personnel self-reporting JP-8 exposure in association with elevated hydrocarbons in the breathing zone ( 28 ). Urinary biomarkers 1- and 2-naphthol, the metabolites of naphthalene, are the most sensitive and useful short-term surrogates of JP-8 exposure due to their strong correlation with breathing zone naphthalene, greater abundance, and slower elimination kinetics ( 29 , 30 ). Blood microRNAs (miRNAs) may be unique biomarkers for volatile organic compounds and have been compared recently to urinary biomarkers in human dockyard workers found to have toluene, xylene, and ethylbenzene in whole blood.…”
Section: Discussionmentioning
confidence: 99%